2022
DOI: 10.1111/hae.14540
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis management and falls prevention in patients with haemophilia: Review of haemophilia guidelines

Abstract: Introduction: Patients with haemophilia (PWH) have a high prevalence of osteoporosis, falls and fractures at all ages. The role of haemophilia itself may contribute to low bone mineral density (BMD) due to coagulation factor deficiency. Guidelines for the management of osteoporosis, fracture and fall risk may help to reduce fracture and fall risk, and delay osteoporosis onset. Aim: We aim to review current haemophilia guidelines regarding osteoporosis prevention, screening, diagnosis and management, and fall p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 73 publications
0
12
1
Order By: Relevance
“…In our study, as many as 49.1% of the haemophilic patients had reduced bone mass. These results are worse than the literature data for adult PWH from recent years, 23–25 which report low BMD in approximately 27%−35% of haemophilic patients. Primary prophylaxis in children with severe haemophilia A was not introduced in Poland until 2008, while secondary prophylaxis in adults has been in place since 2012 2 .…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…In our study, as many as 49.1% of the haemophilic patients had reduced bone mass. These results are worse than the literature data for adult PWH from recent years, 23–25 which report low BMD in approximately 27%−35% of haemophilic patients. Primary prophylaxis in children with severe haemophilia A was not introduced in Poland until 2008, while secondary prophylaxis in adults has been in place since 2012 2 .…”
Section: Discussioncontrasting
confidence: 88%
“…22,23,26 In addition, HBV and HCV hepatotropic virus infections are independent risk factors for the development of secondary osteoporosis. 24,27 This study showed elevated inflammation parameters, including CRP and NLR, which were associated with newly diagnosed active HCV, HBV, and HIV infections and correlated with BMC. Some authors have suggested that NLR is an independent risk factor for the development of osteoporosis in elderly and menopausal women.…”
Section: Discussionmentioning
confidence: 72%
“…However, large-sample prospective drug therapy studies for osteoporosis in PWH are scarce. To date, only one study has evaluated the efficacy of ibandronate for osteoporosis in PWH [ 62 ]. In this study, 10 PWH with osteoporosis received ibandronate treatment for 12 months, and the lumbar spine BMD increased by 4.7%, but no significant change was found in the BMD of the total hip or femoral neck [ 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…PWH have a predisposition to falls because of abnormal joint function, impaired mobility, and poor balance [61]. In PWH, the annual incidence of falls is 32-50%, and 53-81% of fractures are due to falls [62]. The WFH guidelines recommend that musculoskeletal assessment should be performed in adult PWH annually and in pediatric PWH every 6 months [59].…”
Section: Physical Activity and Fall Preventionmentioning
confidence: 99%
“…Despite these limitations, our investigation assessed a large sample of CwH with different disease severity. This investigation contributes to a better understanding of the direct and harmful consequences of decreased musculoskeletal health, 28 including sarcopenia 29 and osteoporosis, 2,3 which result in an increased propensity for falls, 30 fractures, 31 and hospitalizations, and, ultimately, premature death 32 . It is recommended that CwH engage in more physical activity, which may enhance muscle strength and eventually preserve bone strength.…”
Section: Discussionmentioning
confidence: 99%